2020
DOI: 10.1371/journal.pone.0229745
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the gut microbiota of mice orally exposed to methylimidazolium ionic liquids

Abstract: Ionic liquids are salts used in a variety of industrial processes, and being relatively non-volatile, are proposed as environmentally-friendly replacements for existing volatile liquids. Methylimidazolium ionic liquids resist complete degradation in the environment, likely because the imidazolium moiety does not exist naturally in biological systems. However, there is limited data available regarding their mammalian effects in vivo. This study aimed to examine the effects of exposing mice separately to 2 diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 72 publications
0
16
0
Order By: Relevance
“…For example: Liver damage, increase in hepatosomatic index, and modified activities of defense enzymes (CAT, GPX, and GST) have been observed in mouse liver exposed to intraperitoneal injection of [C 8 mim][Br] (Yu et al 2008 ). Marked changes in the gut microbiome have been observed in mice exposed to imidazolium-based ILs via drinking water; however, only mild hepatic and renal effects were observed (Young et al 2020 ). As a system biology potential application of ILs, it has been shown that in rats, oral delivery of a choline-based IL prevent the absorption of fat molecules through intestinal tissue, potentially providing a feeling of satiety (Nurunnabi et al 2019 ).…”
Section: Mechanisms Of Action Of Ilsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example: Liver damage, increase in hepatosomatic index, and modified activities of defense enzymes (CAT, GPX, and GST) have been observed in mouse liver exposed to intraperitoneal injection of [C 8 mim][Br] (Yu et al 2008 ). Marked changes in the gut microbiome have been observed in mice exposed to imidazolium-based ILs via drinking water; however, only mild hepatic and renal effects were observed (Young et al 2020 ). As a system biology potential application of ILs, it has been shown that in rats, oral delivery of a choline-based IL prevent the absorption of fat molecules through intestinal tissue, potentially providing a feeling of satiety (Nurunnabi et al 2019 ).…”
Section: Mechanisms Of Action Of Ilsmentioning
confidence: 99%
“…Marked changes in the gut microbiome have been observed in mice exposed to imidazolium-based ILs via drinking water; however, only mild hepatic and renal effects were observed (Young et al 2020 ).…”
Section: Mechanisms Of Action Of Ilsmentioning
confidence: 99%
“…Ten hours after administration, the authors report histopathological changes in the liver. More recently, oral exposure to M8OI and a related ionic liquid (both as the Cl-salt) in mice have been shown to modulate the gut microbiota ( Young et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Some rodent or human-based studies have confirmed that smoking could result in alterations in community structure and taxonomic abundances in a certain segment of the digestive tract ( Vogtmann et al., 2015 ; Lee et al., 2018 ; Shanahan et al., 2018 ; Al-Zyoud et al., 2019 ; Sublette et al., 2020 ; Tam et al., 2020 ; Young et al., 2020 ; Prakash et al., 2021 ). Our results further confirmed that active smoking could induce a comprehensive effect on community structures and taxonomic abundances in the whole digestive tract.…”
Section: Discussionmentioning
confidence: 99%